The confluence of innovation in therapeutics and regulation: recent cmc considerations (2020)
The field of human therapeutics has expanded tremendously from small molecules to complex biological modalities, and this trend has accelerated in the last two decades with a greater diversity in the types and applications of novel modalities, accompanied by increasing sophistication in drug delivery technology. These innovations have led to a corresponding increase in the number of therapies seeking regulatory approval, and as the industry continues to evolve regulations will need to adapt to the everchanging landscape. The growth in this field thus represents a challenge for regulatory authorities as well as for sponsors. This review provides a brief description of novel biologics, including innovative antibody therapeutics, genetic modification technologies, new developments in vaccines, and multifunctional modalities. It also describes a few pertinent drug delivery mechanisms such as nanoparticles, liposomes, coformulation, recombinant human hyaluronidase for subcutaneous delivery, pulmonary delivery, and 3D printing. In addition, it provides an overview of the current CMC regulatory challenges and discusses potential methods of accelerating regulatory mechanisms for more efficient approvals. Finally, we look at the future of biotherapeutics and emphasize the need to bring these modalities to the forefront of patient care from a global perspective as effectively as possible.